The little mermaid and other tales - Andersen Christian Hans 1805-1875; Hans Christian Andersen (New York : HarperFestival, 2005)
The Little Mermaid is just one jewel in this enchanting collection of twenty stories by the father of the modern fairy tale, Hans Christian Andersen. Whether you prefer laughing aloud at the Emperor in his "new clothes" or sighing as the Little Mermaid pines for her human prince, one thing is certain-this is a book that will be read again and again
Z
1130